Religion, Race, and the Limit of Ethics: Historical Considerations - Dees, Sarah E. (Journal of religious ethics, 2024)
This article examines the study of Indigenous religions and ethics in the late-nineteenth and early-twentieth centuries. Over the past few decades, scholars have grappled with the colonial origins of religious studies. This essay focuses on the history of anthropological scholarship on Indigenous religions and the significance of this work for the growth of the academic study of religious and ethical systems. I first consider scholarship on Indigenous ethical systems produced by theologians and comparative religionists. I next consider how anthropological concepts of cultural relativity offered scholars of religion important tools to broaden and deepen understandings of Indigenous cultures. Finally, I address the limits of these anthropological tools. During this era, scholars increasingly argued that Indigenous cultural traditions were worthy of study; however, the prevailing racialized assumptions contributed to assessments of these ethical systems as inferior to Euro-American religio-ethical systems.